BRAND SWITCHING PENGGUNA SIM CARD SIMPATI - Nurul Farida, - (2019)
This research is a quantitative research that aims to determine the effect of price, advertising, and product attributes on brand switching. The population in this study were Simpati users in One Belpark Mall. The sample size was taken as many as 75 respondents, with a non probability sampling method with a purposive sampling method. Data collection is done through the distribution of questionnaires. The analysis technique used is the method of PLS (Partial Least Square) analysis with SmartPLS3.0 software. The results of this study indicate that (1) Price has a positive and significant influence on brand switching with path coefiient 0,558. (2) Advertising has a positive and significant to brand switching with path coefiient 0,948. (3) Product attributes has a negative and significant influence on brand switching with path coefiient -0,590.